The nature and impact of climate change in the Challenge Program on Water and Food (CPWF) basins - Mulligan, M.; Fisher, M.; Sharma, B.; Xu ZX; Ringler, Claudia; Mahe G; Jarvis, Andy; Ramírez Villegas, Julián Armando; Clanet, J.C.; Ogilvie, A.; Ahmad, M. (Informa UK Limited, 2011)
In this article the authors assess the potential impacts of projected climate change on water, livelihoods and food security in the Basin Focal Projet basins. The authors consider expected change within the context of recently observed climate variability in the basins to better understand the potential impact of expected change and the options available for adaptation. They use multi-global circulation model climate projections for the AR4 SRES A2a scenario, downscaled and extracted for each basin. They find significant differences in the impacts (both positive and negative impacts) of climate change, between and within basins, but also find large-scale uncertainty between climate models in the impact that is projected.